90 Years of New “Namban” Culture: Spanish References in the Works of Japanese Creators (Comillas Journal of International Relations, 2020)
Japanese appreciation for Dalí, Picasso, Miró, Dalí, Falla, Albéniz and, especially, Gaudí and flamenco is well-known. There is, however, influence and presence of Spanish culture in some most relevant Japanese creators which goes beyond that and is not so well known. This brief essay highlights a few examples, in fields such as performing arts, cinema, photography or architecture.
Keywords: Nanban; butoh; Gaudí; Kazuo Ohno; Hiroshi Teshigahara; Fernando Higueras; Hiroshi Naito; Ikko Narahara; Japan